Answer:
<span>−143231</span>
Explanation:
The general term of a geometric series can be described by the formula:
<span><span>an</span>=a<span>r<span>n−1</span></span></span>
where the initial term is a and common ratio r.
Then we find:
<span><span><span>(1−r)</span><span><span>N∑</span><span>n=1</span></span><span>an</span></span><span><span>=<span><span>N∑</span><span>n=1</span></span>a<span>r<span>n−1</span></span>−r<span><span>N∑</span><span>n=1</span></span>a<span>r<span>n−1</span></span></span><span>=a+<span><span><span>N∑</span><span>n=2</span></span>a<span>r<span>n−1</span></span></span>−<span><span><span>N∑</span><span>n=2</span></span>a<span>r<span>n−1</span></span></span>−a<span>rN</span></span><span>=a<span>(1−<span>rN</span>)</span></span></span></span>
So dividing both ends by <span>(1−r)</span> we find:
<span><span><span>N∑</span><span>n=1</span></span><span>an</span>=<span><span>a<span>(1−<span>rN</span>)</span></span><span>1−r</span></span></span>
In our example, <span>N=7</span>, <span>a=−11</span> and <span>r=−5</span>
So:
<span><span><span><span>7∑</span><span>n=1</span></span><span>(−11)</span><span><span>(−5)</span><span>n−1</span></span></span><span>=
</span></span>